Exploring the Influence of Vocabulary Range on Speaking Skills: Insights from the Fun English Club Bale Inggris Selong - Andini, Nida; Assapari, Mugni (English Education, Linguistics, and Literature Journal, 2025)
This research aims to determine the impact oflexicon size on oral proficiency at Fun English Club Bale InggrisSelong. This research is quantitative a type of explanatory sequentialdesign. The population in the research was 40 members of the FunEnglish Club. The sampling technique used total sampling. The datacollection techniques used were assessment, testing, and surveys. Thetest for knowing the lexicon size of members’ Fun English Club wasthe website preply.com English Test Vocabulary and for test oralproficiency was used to tell a story where the member chose one topicout of four topics from the researcher. The data analysis technique inthis research used a t-test. Based on the results of the t-test testing thathas been carried out, it can be concluded that there is an impact oflexicon size on the oral proficiency of members of Fun English Club(t = 2.745; p < 0.05). This suggests that having a bigger lexiconimproves oral competency greatly, stressing the importance ofvocabulary in efficient communication. Particularly in languageacquisition and fluency.